2012
DOI: 10.1016/s0140-6736(12)60150-0
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative colitis

Abstract: Ulcerative colitis is an idiopathic, chronic inflammatory disorder of the colonic mucosa, which starts in the rectum and generally extends proximally in a continuous manner through part of, or the entire, colon; however, some patients with proctitis or left-sided colitis might have a caecal patch of inflammation. Bloody diarrhoea is the characteristic symptom of the disease. The clinical course is unpredictable, marked by alternating periods of exacerbation and remission. In this Seminar we discuss the epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
1,229
2
70

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,717 publications
(1,309 citation statements)
references
References 139 publications
8
1,229
2
70
Order By: Relevance
“…Although the exact etiology of ulcerative colitis remains unknown, a combination of genetic predisposition and environmental risk factors underlie its pathogenesis. 7 Unlike the findings from our study, Molodecky et al 2 found that ulcerative colitis appears to be on the rise around the globe. Ulcerative colitis is more prevalent in developed nations, with the highest prevalence in Europe (51 per 10,000 persons) and North America (25 per 10,000 persons).…”
Section: Discussioncontrasting
confidence: 85%
“…Although the exact etiology of ulcerative colitis remains unknown, a combination of genetic predisposition and environmental risk factors underlie its pathogenesis. 7 Unlike the findings from our study, Molodecky et al 2 found that ulcerative colitis appears to be on the rise around the globe. Ulcerative colitis is more prevalent in developed nations, with the highest prevalence in Europe (51 per 10,000 persons) and North America (25 per 10,000 persons).…”
Section: Discussioncontrasting
confidence: 85%
“…At diagnosis, UC patients presented with the following disease extent: proctitis [199 patients (21.7%)], left-sided colitis [338 patients (36.8%)] and extensive colitis/pancolitis [381 (41.5%)]. During a median disease duration of 9 [4][5][6][7][8][9][10][11][12][13][14][15][16] years, progression and regression was documented in 145 patients (15.8%) and 149 patients (16.2%) respectively. In addition, 624 patients (68.0%) had a stable disease extent.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Ulcerative colitis is thought to develop as a consequence of a dysregulated mucosal immune response to commensal gut flora in genetically susceptible individuals. 3,4 Roughly, one-third of newly diagnosed UC patients initially presents with ulcerative proctitis/proctosigmoiditis. 5,6 Another third of newly diagnosed patients presents with left-sided colitis at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 20–30% of patients with ulcerative colitis (UC) require surgery at some stage of their disease 1. Indications for surgical treatment of UC include chronic refractory disease despite optimal medical therapy, corticosteroid dependence, complications of medical therapy, acute severe UC, and development of colorectal dysplasia or malignancy.…”
Section: Introductionmentioning
confidence: 99%